The effects of stress and segmentation preferences on employee well-being and work-life balance in the context of remote work - Ahmadov, Murad (ADA University, 2022)
The COVID-19 pandemic has radically changed the modern workplace, introducing a forced, long-term, mass shift of many employees to a remote working mode. This has presented an opportunity to study the relationships of many factors traditionally used in research within this field in a new context. Therefore, this study has evaluated the impact of stress and segmentation preferences of employees on their well-being and work-life balance in the context of remote work during a worldwide COVID-19 pandemic. Following an analysis of cross-sectional survey data collected from 249 working adults within the city of Baku, Azerbaijan in April-May 2022, several causal effects of stress and segmentation on the chosen factors has been established. The findings have shown the existence of a direct negative causal relationship of stress on work-life balance and its effect on deterioration of well-being, represented by depression and insomnia. It was further found that high segmentation preferences cause an improvement of work-life balance as well as an increase in depression. The results of this study contribute to the field of remote work, highlighting links between traditional factors in a non-voluntary remote work context and offering new avenues for research, while also providing insights to management and human resource professionals into the causes of important aspects within a new work environment.
Keywords: Remote work.; Remote work -- COVID-19.; Segmentation preferences.; Business